Effects of uncertainties in probabilistic seismic hazard analysis on response of a tall building - Şenkardeşler, Oğuz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Structures in seismic regions are designed to withstand the seismic demands imposed by ground motions. Design of a tall building is usually performed with an extra care due to the amount of investments done for the construction and also the possible consequences in case of an undesired structural damage. Special care is needed for the estimation of seismic demand since the design of a structure is generally governed by seismic forces in seismic-prone regions. Finite element model (FEM) of the structure is expected to ful ll the target response requirements under selected ground motions in order to satisfy the requirements of a properly designed structure. Ground motion records used in the analyses should be selected in accordance with the seismic hazard results expected at the site of the structure. Seismic hazard of a site can be determined via probabilistic seismic hazard analysis (PSHA). PSHA utilizes seismicity models and ground motion prediction equations (GMPEs) to calculate hazard levels. Seismicity models are very sensitive to uncertainties, so as the hazard levels. These uncertainties and their e ects on seismic hazard estimations are investigated in this study. By conducting linear time-history analyses with the selected ground motions on a 43-story reinforced concrete tall building in Istanbul, the e ects of these uncertainties on the response of a tall building is also investigated. In order to validate the FEM, structure is instrumented with accelerometers and system identi cation (SID) is conducted with ambient vibration measurements. In addition to the seismic hazard calculations, structural models have uncertainties as well due to the assumptions and subjective decisions in modeling phase. It is crucial to validate the FEM or update the FEM according to SID results in order to catch a realistic behavior of the real structure.
Keywords: Earthquake hazard analysis.